Arterial spin labeling compared to dynamic susceptibility contrast MR perfusion imaging for assessment of ischemic penumbra: A systematic review. Issue 6 (13th August 2021) - Liu, Jinyuan; Lin, Christopher; Minuti, Aurelia; Lipton, Michael
Abstract: Background and Purpose: Dynamic susceptibility contrast (DSC) MR imaging is commonly used to estimate penumbra size in acute ischemic stroke; this technique relies on the administration of gadolinium contrast, which has limited use in certain populations, such as those with impaired renal function or allergies. Arterial spin labeling (ASL) is a relatively new technique that can provide information on cerebral perfusion without need for exogenous contrast agents. This systematic review examines published studies that specifically compared ASL to DSC for assessment of ischemic penumbra. Methods: We searched PubMed, Embase, Web of Science, and the Cochrane Library for papers which compared ASL with DSC for assessment of ischemic penumbra in acute ischemic stroke among adult human populations. Two independent reviewers screened studies using predefined inclusion and exclusion criteria. Study characteristics and findings regarding the utility of ASL compared to DSC for identification of penumbra were then extracted and anlyzed for results and risk of bias. Results: Seventeen articles met inclusion and exclusion criteria. Studies compared ASL with DSC on a range of metrics (hypoperfusion, hyperperfusion, mismatch, and reperfusion). Most studies concluded that agreement of ASL with DSC was moderate to very high. A small subset of studies found discrepancy in agreement of ASL with DSC for size or location of perfusion abnormalities. A heterogeneity of perfusion parameters studied for DSC was noted, along with the need for more standardization of research methods . Conclusion: ASL shows moderate to high agreement with DSC for detection of penumbra among ischemic stroke patients.